APPLICATION OF QUANTUM MECHANICS AND PROBABILITY THEORY IN RADIOACTIVE DECAY - Qoshniyazova Sh.Y; Jollıbekov B.R (Western European Studies, 2025)
Radioactive decay is a fundamental process of nuclear physics, characterized by the random transformation of unstable nuclei and the release of particles and radiation. This article analyzes in detail the probabilistic nature of radioactive decay from the perspective of probability theory and quantum mechanics. The mathematical derivation of the classical decay law and the exponential distribution of nuclei over time are shown. The quantum mechanical mechanism of alpha decay and the tunneling effect are also analyzed using the Schrödinger equation. Beta and gamma decays are briefly described based on quantum field theories. The article is intended for students and researchers to study the main aspects of nuclear physics.
Keywords: quantum mechanics; radioactive decay; tunneling effect; exponential distribution